International Legal Aspects of Tourism Activity: International Treaties Analysis - ABAYDELDINOV, Yerbol; KALA, Nagima (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016DO - 10.14505/jarle.v7.4(18).01, 2016)
The present paper illustrates the general characteristics of acts of international law in the sphere of international tourism. International tourism has become an independent sphere of interstate cooperation and an effective instrument of international communication. The development of international tourism activities demands that states settle such existing issues as facilitating tourism formalities, liberalizing tourism services, unifying and harmonizing the legal regulation of tourism activities, protecting the environment from adverse influences of international tourism, and ensuring tourists’ rights, among others. The settlement of these issues can only be approached legally through international treaties. Thus, this paper attempts to analyse international conventions on tourism customs issues, international instruments on the trade in tourism services, and international treaties on space and tourism in Antarctica.